2006
DOI: 10.2215/cjn.01480506
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cardiovascular Disease in Children and Young Adults after Renal Transplantation

Abstract: Despite good outcomes in pediatric renal transplantation, life expectancy is reduced, mostly as a result of accelerated atherosclerosis. A comprehensive evaluation of cardiac status and risk factors for cardiovascular disease was performed in 60 patients after renal transplantation (age 3 to 29 yr; mean 15.8). Posttransplantation diabetes was diagnosed in 7%. Half of the patients did not engage in any physical activity, and this was associated with increased body mass index. Uncontrolled hypertension was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 41 publications
5
35
1
Order By: Relevance
“…a value slightly lower than what was found in the present study. Becker-Cohen et al 38 evaluated the 6MWT in children and young adults with CKF and with kidney transplants who were still undergoing dialysis. They found values within normality and, although there were no specific predictive values for children, they found that on average, the distance that they were able to walk was only 100 meters less than what the adults who were evaluated could achieve.…”
Section: Discussionmentioning
confidence: 99%
“…a value slightly lower than what was found in the present study. Becker-Cohen et al 38 evaluated the 6MWT in children and young adults with CKF and with kidney transplants who were still undergoing dialysis. They found values within normality and, although there were no specific predictive values for children, they found that on average, the distance that they were able to walk was only 100 meters less than what the adults who were evaluated could achieve.…”
Section: Discussionmentioning
confidence: 99%
“…We defined normal LDL as <100mg/dL, in keeping with recent studies; the more stringent cutoff is recommended for high-risk populations of children and young adults. 32,33 The mean age of our survivors was >20 years. Body surface area (BSA) was calculated as (W 0.425 3 H 0.725 ) 3 0.007184, where W is the weight in kilograms and H is the height in centimeters; BSA was categorized as low (<1.62 m 2 ), normal (1.62-1.99 m 2 ), or high (2-2.90 m 2 ) according to recent recommendations.…”
Section: Perceived Physical Healthmentioning
confidence: 99%
“…26 Plasma homocysteine levels are higher with cyclosporine than tacrolimus. 27 This has been shown at 6 and 12 months after kidney transplant, and homocysteine values are closely related to serum creatinine in patients receiving cyclosporine or tacrolimus. 28 The endothelium controls coagulation, fibrinolysis, vascular tone, and immune response, and endothelial dysfunction may be caused by inflammation, retention of L-arginine inhibitors, oxidative stress, hyperhomocysteinemia, dyslipidemia, hyperglycemia, and hypertension.…”
Section: Discussionmentioning
confidence: 92%